Confirmatory Factor Analysis of Warr, Cook, and Wall's (1979) Job Satisfaction Scale - Heritage, B.; Pollock, C.; Roberts, Lynne (Taylor and Francis Ltd., 2015)
Warr, Cook, and Wall's Job Satisfaction Scale (JSS) is a widely used measure of job satisfaction in industrial/organisational (I/O) psychology research and practice. However, the factor structure has not been adequately explored, with two-factor and three-factor solutions previously proposed. This study tested the factor structure of the JSS using robust analysis methods on data gathered from a convenience sample of 381 (females=264, males=116) Australian employees. Confirmatory factor analyses supported a hierarchical three-factor model of job satisfaction in terms of model adequacy coefficients; however, the three factors were highly correlated, thereby rendering a multifactorial approach to the JSS untenable. The results support the continued use of an overall score of job satisfaction when using this measure in I/O psychology research and practice. Further testing of the structure is recommended within a range of employment sectors, as the assumed multifactorial structure of the JSS common in the literature was not supported by the current study.